Sustainable development: the Nexus of Environmental Sustainability, Values, and Ethics - CHOY, Yee Keong (European Journal of Sustainable Development, 2017)
The paper seeks to redesign the disciplines of sustainable development by establishing a new ethical-ecological order based on value pluralism and environmental ethics. The argument begins with identifying the failure of the Brundtland Report in addressing the fundamental premise for sustainability which is the need to adopt non-anthropocentric attitudes towards nature. It then moves for restoring an ethical human relationship with the non-human natural world. Citing empirical evidence from research conducted in the forests of Borneo, the paper concludes that for sustainable development to be a useful concept, it must embrace the ethical dimension of sustainability rather than merely targeting its classical aim of meeting “the needs of the present without compromising the ability of future generations to meet their own needs”. Key words: Brundtland Report, intergenerational equity, environmental sustainability, environmental ethics